The effects of response mode and importance on decision-making strategies: Judgment versus choice - Billings, Robert S; Scherer, Lisa L (Organizational behavior and human decision processes, 1988)
Judgment and choice have not always been clearly distinguished, and there is little direct research on their effects on the decision process. As compared to choice, judgment is predicted to lead to more information searched, a less variable pattern of search, and a greater amount of interdimensional search. In essence, search processes that imply elimination by aspects will occur more often under choice than judgment. It is further argued that a number of variables may moderate this response mode effect. The potential moderator examined here is decision importance, which is predicted to produce analytical judgment processes prior to choice. Using an information search board, 104 subjects made decisions (choices or judgments) on candidates for residence hall advisor, under high or low decision importance. Response mode produced strong effects on all measures of the decision process. Importance had fewer effects; it affected the frequency of an intradimensional/variable search mode, but moderated the response mode effect only for amount of information searched. Given these results, several implications follow. Research which uses ajudgment response (e.g., policy capturing) should not be generalized to choice tasks. Also, requiring an explict judgment even when only the final choice matters may be a useful procedure. Further research is needed to examine the effects of response mode on additional outcomes, such as how the information is organized in memory and which alternative is actually selected.